Cerebellar-limbic dysregulation and sensorimotor network alterations in male primary insomnia: a resting-state functional magnetic resonance imaging study - Lu, Juan; Yuan, Zhengzhen; Hu, Jidan; Yue, Jiajun; Jie, Pingping; Liu, Yong; Zhang, Haiyi; Zhao, Jie (Frontiers in Human Neuroscience, 2025)
ObjectiveThe neuropathological mechanisms specific to male insomnia disorder (ID) remain underexplored, particularly regarding intrinsic brain activity patterns. Using functional magnetic resonance imaging (fMRI), this study aims to investigate the characteristics of amplitudes of low-frequency fluctuations (ALFF) and regional homogeneity (ReHo) in male patients with primary ID, and to explore the correlations between these neuroimaging indicators and sleep scale scores.MethodsA total of 30 male patients diagnosed with ID and 30 age-matched healthy controls (HCs) were enrolled. All participants underwent standardized assessments with the Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), and Hamilton Depression Scale (HAMD). Resting-state functional magnetic resonance imaging (rs-fMRI) was utilized to assess regional brain activity abnormalities in male insomnia patients through amplitude of low-frequency fluctuations (ALFF) and regional homogeneity (ReHo) analyses. Statistical correlations between aberrant ALFF/ReHo values and clinical scale scores were subsequently examined.ResultsPatients with ID showed significantly higher scores on the PSQI, HAMD Rating Scale score, and the ISI, compared with HCs. fMRI results revealed that, relative to HCs, ID patients exhibited reduced ALFF in the Precentral_R and increased ALFF in the Cerebelum_6_R and Temporal_Inf_L (p < 0.05, cluster level-FWE corrected). Regarding ReHo, patients displayed elevated ReHo values in the Temporal_Inf_L, Cerebelum_6_R, and Hippocampus_R, whereas decreased ReHo values were observed in the Putamen_L, Insula_R, and Calcarine_R (p < 0.05, cluster level-FWE corrected). However, neither ALFF nor ReHo measures demonstrated significant correlations with clinical scale scores (p > 0.05).ConclusionMale patients with ID exhibit functional abnormalities in the cerebellum-limbic system circuit and the sensorimotor network. These alterations are accompanied by impaired motor coordination, dysregulated emotional processing, and deficits in sensory integration. Although ALFF and ReHo metrics show no significant correlation with the severity of clinical symptoms, the regional distribution patterns of these indicators across different brain areas suggest that they may serve as an index for ID, rather than a direct reflection of symptomatic manifestations.